Kesenian rakyat gandrung dari Banyuwangi - Sularto, B. (Bambang) (Proyek Pengembangan Media Kebudayaan, Departemen Pendidikan dan Kebudayaan, 1975)
On traditional dances and music of Banyuwangi, Jawa Timur.